2007
DOI: 10.4161/chan.4321
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of PLC-Mediated Kir3 Current Inhibition

Abstract: A large number of ion channels maintain their activity through direct interactions with phosphatidylinositol bisphosphate (PIP 2 ). For such channels, hydrolysis of PIP 2 causes current inhibition. It has become controversial whether the inhibitory effects on channel activity represent direct effects of PIP 2 hydrolysis or of downstream PKC action. We studied Phospholipase C (PLC)-dependent inhibition of G protein-activated inwardly rectifying K + (Kir3) channels. By monitoring simultaneously channel activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Hydrolysis of PIP 2 has been indeed suggested as a contributing mechanism to the slow time-scale desensitization of K ACh currents in response to ACh in cardiac myocytes and heterologous expression systems. 47,48 The durations of the openings and bursts of Kir channels displayed different sensitivities to PIP 2 levels. Our single-channel studies of Kir3.4*-S176P suggested that the open-time kinetics of appeared to depend on the specific batch of oocytes used, which made a rigorous characterization difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis of PIP 2 has been indeed suggested as a contributing mechanism to the slow time-scale desensitization of K ACh currents in response to ACh in cardiac myocytes and heterologous expression systems. 47,48 The durations of the openings and bursts of Kir channels displayed different sensitivities to PIP 2 levels. Our single-channel studies of Kir3.4*-S176P suggested that the open-time kinetics of appeared to depend on the specific batch of oocytes used, which made a rigorous characterization difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The net downstream effect of PKC activation on Kir3 channels is current inhibition, allowing for increased cellular excitability (Stevens et al, 1999;Mao et al, 2004;Keselman et al, 2007). Gq-coupled receptor activation also simultaneously depletes the local concentration of PIP 2 by hydrolysis to IP 3 , which decreases Kir3 channel activity because PIP 2 is a required component for activation of Kir3 channels (Huang et al, 1998;Zhang et al, 1999). The combination of PKC activation and PIP 2 depletion acts in concert to further inhibit Kir3 channel activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, others [15,23,32,36] suggest that the downstream activation of PKC underlies the inhibition of I K,ACh . There are also some pieces of evidence to suggest that reduction in membrane PIP 2 and PKC activation are both involved in the I K,ACh inhibition by agonists such as carbachol [22] and ACh [17].…”
Section: Discussionmentioning
confidence: 99%